2006
DOI: 10.1248/bpb.29.2465
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human P-Glycoprotein (MDR1/ABCB1) ATPase Activity Assay Method by Comparing with in Vitro Transport Measurements: Michaelis-Menten Kinetic Analysis to Estimate the Affinity of P-Glycoprotein to Drugs

Abstract: Human ABC transporter P-glycoprotein (P-gp/ABCB1) encoded by the multidrug resistance (MDR1) gene is recognized as one of the most important factors regulating pharmacokinetics of a number of clinically important drugs because of its function of extruding a wide range of structurally unrelated amphiphilic and hydrophobic drugs from the inside to the outside of cells in an ATP-driven mechanism. In the present study, we have evaluated the high-speed ATPase activity assay method by comparing with in vitro transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…By using the series of same cell lines, Katoh et al (2006) examined the species differences in maximal activity (V max / K m ) of P-gp to transport its substrate drugs and clarified the fact that maximal activity of rat MDR1b correlated well with that of human MDR1. In addition, the apparent K m value of quinidine to rat MDR1a was reported to be approximately 5 M (Müller et al, 1994) and corresponded well with that of human MDR1 in other reports [5.42 M by Adachi et al (2001) and 7.88 M by Shirasaka et al (2006b)]. On the basis of these facts, it is possible to validate our method by simulating the concentration-dependent permeability of three P-gp substrate drugs to rat small intestine and then by comparing the results of simulation with the experimentally measured permeability of those drugs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…By using the series of same cell lines, Katoh et al (2006) examined the species differences in maximal activity (V max / K m ) of P-gp to transport its substrate drugs and clarified the fact that maximal activity of rat MDR1b correlated well with that of human MDR1. In addition, the apparent K m value of quinidine to rat MDR1a was reported to be approximately 5 M (Müller et al, 1994) and corresponded well with that of human MDR1 in other reports [5.42 M by Adachi et al (2001) and 7.88 M by Shirasaka et al (2006b)]. On the basis of these facts, it is possible to validate our method by simulating the concentration-dependent permeability of three P-gp substrate drugs to rat small intestine and then by comparing the results of simulation with the experimentally measured permeability of those drugs.…”
Section: Discussionsupporting
confidence: 87%
“…This finding might be explained by its high permeability (high P app, PD ), high affinity to P-gp (low K m ), and/or low V max compared with other drugs, as shown in Fig. 2B (Borgnia et al, 1996;Adachi et al, 2001;Troutman and Thakker, 2003;Shirasaka et al, 2006b). Ogihara et al (2006) investigated the influence of P-gp on the intestinal absorption of verapamil in each intestinal segment in wild-type and mdr1a/1b gene-deficient mice, whereas no significant effects of P-gp on the absorption of verapamil were observed in all intestinal segments.…”
Section: Downloaded Frommentioning
confidence: 97%
“…A "true" P-gp inhibitor is defined as one which inhibits P-gp without being effluxed by P-gp itself and simultaneously does not activate ATPase 16 . In the P-gp-Glo assay system, a significant decrease in residual ATP content was produced by VER (a P-gp substrate and competitive inhibitor) while a significant increase in inhibited it, consistent with previous results 17 . We then found that trantinterol produced an increasing tendency in residual ATP content especially at concentrations of 10 µM and 100 µM (P<0.01) (Figure 4).…”
Section: P-gp Expression Validationsupporting
confidence: 91%
“…Also, its expression has been described in lymphoid cell populations from human bone marrow and peripheral blood (5). Specifically, it has been shown on the membrane of pluripotent stem cells, monocytes, dendritic cells, CD4 + and CD8 + T lymphocytes, NK cells, and B lymphocytes, suggesting that Pgp may influence cell-mediated immune responses (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%